Religion And Election: An Ethnographic Account Of Two Caleg Ustadz - Ahmad Muhajir (JOURNAL OF ISLAMIC AND LAW STUDIES, 2021)
Abstract: In the literature, of many practices that have been analysed in relation to religion, vote buying has received little attention. The existing work tend to normatively analyse religious texts that the authors see fit to vote buying and come up with the expected verdict, namely, Islam prohibits the practice. But there is another important question of whether religious people actually follow the religious guidance on vote buying. This paper is part of a series of empirical studies on the behaviour of religious candidates in an election where vote buying was rampant. Through the case of two Islamic teachers who ran as legislative candidates (caleg ustadz), I show that religion does not necessarily inspire a clean politics. Nevertheless, their case also indicates that religion still functions as a prism to view the election results. Abstrak: Di dalam literatur, dari sekian banyak praktik yang telah dianalisis dalam kaitannya dengan agama, praktik jual-beli suara dalam pemilu kurang mendapat perhatian. Karya-karya yang ada cenderung secara normatif menganalisis teks-teks agama yang dianggap penulisnya tepat untuk politik uang dan menghasilkan kesimpulan yang telah dapat ditebak sebelumnya, yaitu Islam melarang praktik tersebut. Namun ada pertanyaan penting lainnya, yakni apakah umat beragama benar-benar mengikuti tuntunan agama dalam urusan jual-beli suara dalam pemilu. Tulisan ini merupakan bagian dari rangkaian studi empiris tentang perilaku caleg relijius di dalam konteks pemilu yang sarat politik uang. Melalui kasus dua ustadz yang maju sebagai calon legislatif (caleg), saya menunjukkan bahwa agama tidak serta merta menginspirasi politik yang bersih. Namun demikian, agama tampaknya masih berfungsi sebagai teropong untuk memahami hasil pemilu.